Changes in fine root production and longevity in relation to water and nutrient availability in a Norway spruce stand in northern Sweden - Majdi, Hooshang (Tree Physiology, 2001)
Effects of irrigation and liquid fertilization on fine root (< 1 mm) production and longevity, and fine root (< 0.5–2 mm) biomass were studied in a Norway spruce ( Picea abies (L.) Karst.) stand in northern Sweden. Fine root length production and longevity were measured by the minirhizotron technique at 0–10 cm depth in the following treatments: irrigation (I), liquid fertilization (IL) and control (C). Standing root biomass and root length density (RLD) were studied in the litter–fermented humus (LFH) layer and at depths of 0–10, 10–20 and 20–30 cm using soil cores in solid fertilized (F) and C plots. Minirhizotrons were installed in October 1994 and measurements recorded monthly from July to September 1995 and during the growing season in 1996. Soil cores were sampled in 1996. Fine root production increased significantly in IL plots compared with C plots, but the I treatment did not increase root production. Root mortality increased significantly in IL plots compared with C plots. Fine root longevity in IL plots was significantly lower compared with C and I plots. No significant difference was found between longevity of fine roots in I and C plots. Compared with C, F treatment increased fine root biomass in the LFH and mineral soil layers, and increased the amount of fine roots in mineral soil layers relative to the LFH layer. Furthermore, F increased RLD and the number of mycorrhizal root tips significantly.